Protecting Consumer Protection - Lai, Jessica C; Becher, Samuel I (Victoria University of Wellington Law Review, 2018)
Recent consumer law cases are shaping consumer law in an unwarranted way. The courts have acknowledged the importance of advancing consumer law and protecting consumers, however, upon closer examination it is questionable whether courts are employing the right framework, tools and considerations. By analysing recent country of origin cases this article identifies some potentially worrying ways in which the courts have eroded consumer law rather than strengthening it. In particular, such cases allow the proprietary interest of goodwill to creep into the Fair Trading Act 1986 (FTA). Doing so, even if only at the stage of determining the penalty to be imposed, may shift the dial further towards the Fair Trading Act (FTA) being a means for protecting traders’ interests. This, in turn, may lead to negative unintended consequences.